Achieving the UNAIDS 95-95-95 treatment target by 2025 in Ghana: a myth or a reality? - Dorothy Serwaa Boakye; Samuel Adjorlolo (Taylor & Francis Group, 2023)
The United Nations Joint Programme on HIV/AIDS (UNAIDS) has set ambitious treatment targets known as Project 95-95-95, aiming to achieve 95% of people living with HIV knowing their status, 95% of diagnosed individuals on antiretroviral therapy (ART), and 95% of those on ART achieving viral suppression by 2025. Through a comprehensive analysis of Ghana's HIV/AIDS response, we evaluate the feasibility of Ghana's efforts in realising these targets. The discussion explores Ghana's achievements in HIV testing and diagnosis, ART coverage, and viral suppression rates, as well as challenges related to stigma, limited access to healthcare services, funding constraints, and data quality. Strategies such as strengthening prevention efforts, expanding access to ART, addressing stigma, and enhancing health systems are discussed as the way forward to advance Ghana's progress towards the UNAIDS 95-95-95 treatment targets. While Ghana has made significant strides in its HIV/AIDS response, achieving the 95-95-95 targets is a challenging yet realistic goal.